Procalcitonin-guided antibiotic therapy in intensive care unit patients: a systematic review and meta-analysis - Hui-Bin Huang (Annals of Intensive Care, 2017)
Abstract Background Serum procalcitonin (PCT) concentration is used to guide antibiotic decisions in choice, timing, and duration of anti-infection therapy to avoid antibiotic overuse. Thus, we performed a systematic review and meta-analysis to seek evidence of different PCT-guided antimicrobial strategies for critically ill patients in terms of predefined clinical outcomes. Methods We searched for relevant studies in PubMed, Embase, Web of Knowledge, and the Cochrane Library up to 25 February 2017. Randomized controlled trials (RCTs) were included if they reported data on any of the predefined outcomes in adult ICU patients managed with a PCT-guided algorithm or according to standard care. Results were expressed as risk ratio (RR) or mean difference (MD) with accompanying 95% confidence interval (CI). Data synthesis We included 13 trials enrolling 5136 patients. These studies used PCT in three clinical strategies: initiation, discontinuation, or combination of antibiotic initiation and discontinuation strategies. Pooled analysis showed a PCT-guided antibiotic discontinuation strategy had fewer total days with antibiotics (MD − 1.66 days; 95% CI − 2.36 to − 0.96 days), longer antibiotic-free days (MD 2.26 days; 95% CI 1.40–3.12 days), and lower short-term mortality (RR 0.87; 95% CI 0.76–0.98), without adversely affecting other outcomes. Only few studies reported data on other PCT-guided strategies for antibiotic therapies, and the pooled results showed no benefit in the predefined outcomes. Conclusions Our meta-analysis produced evidence that among all the PCT-based strategies, only using PCT for antibiotic discontinuation can reduce both antibiotic exposure and short-term mortality in a critical care setting.